THE IMPACT OF WIRELESS HEADPHONES ON THE CENTRAL NERVOUS SYSTEM (The Conference Hub, 2025)
In recent years, wireless headphones have become an integral part of everyday life, significantly simplifying the use of audio devices and providing mobility.